Model of self-esteem during adolescence period - Olivera Kalajdžić; Ranka Perućica (Биомедицинска истраживања, 2018)
In contemporary psychological literature, there is a huge amount of research concerning self-esteem as well as the importance of high or low level of it for the adaptive and maladaptive behavior of a person. Self-esteem is defined as the result of one's self-conception and self-evaluation, respectively. It is extremely important during adolescence when the changes in experience and behavior are often crucial for future life, personal self-satisfaction, relationships with other people, as well as for the success in the activities and roles they are taking. Researchers within this field claim that behavior, as well as the adolescents' abilities, are always consistent with their self-image. Self-esteem is an important component of healthy adolescent's development and of a successful transition to the adult world. For this reason, in this paper we will define the notion of self-esteem, explain the dimensions and importance of it, and outline the results of recent research concerning the adolescent population.
Keywords: self-esteem; adolescence; development of self-esteem; importance of self-esteem